Mechanics Properties on Glass Fiber Reinforced Polymer-Confined Concrete Short Columns - Wang, Juan; Zhao, Junhai; Zhu, Qian; Li, Nan (Asian Journal of Chemistry, 2014)
Based on the unified strength theory, considering the intermediate principal stress and the hooping effect of glass fiber reinforced polymer (GFRP) tube and stirrup to analyze the strength of concrete and section steel under triaxial compression, formulas of axial bearing capacities on two kinds of cross-section for GFRP-confined concrete short columns are proposed. By using nonlinear finite element ANSYS program, the establishment process of models is introduced in detail on such two types composite columns. Then, the axial ultimate bearing capacities and the complete stress-strain curves for members are obtained. In comparison with test results from the references, theoretical calculation results and numerical simulation results are satisfactory. Finally influences of loads on the stress distribution and the concrete strength and longitudinal reinforcement ratio on bearing capacities for members are studied.